Random House Webster's College Dictionary (Random House Webster's College Dictionary - Random House (Random House, 2000)
Webster's annually updated dictionary offers an outstanding blend of new-millennium lingo and the classic words and origins of the English language. For instance, it includes extensive computer terminology, such as bot, cookie, and terabyte, as well as cyberjargon, such as clicks-and-mortar ("adj. pertaining to being a company that does business on the Internet and in traditional stores or offices"). It even has slang listings for my bad! ("slang. my fault! my mistake!") and senior moment ("n. ((often facetious)) a brief lapse in memory or moment of confusion, esp. in an older person"). Inclusions like these appeal especially to generation X and even generation Y ("n. the generation born in the 1980s and 1990s, especially in the United States").